2020
DOI: 10.3390/cancers12051147
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Extracellular Vesicles Convey Protein Signatures That Reflect Pathophysiology in Lung and Pancreatic Adenocarcinomas

Abstract: Using a combination of mass-spectrometry and aptamer array-based proteomics, we characterized the protein features of circulating extracellular vesicles (EVs) in the context of lung (LUAD) and pancreatic ductal (PDAC) adenocarcinomas. We profiled EVs isolated from conditioned media of LUAD and PDAC cell lines to identify EV-associated protein cargoes released by these cancer cell types. Analysis of the resulting data identified LUAD and PDAC specific and pan-adenocarcinoma EV protein signatures. Bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…sEVs are secreted from all cell types and present in all body fluids. Because sEVs are higher in number and with diameters below 200 nm smaller in size than CTCs, they are easier to separate from blood cells, and their membrane protects their cargo, allowing for reproducible analysis after storage [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…sEVs are secreted from all cell types and present in all body fluids. Because sEVs are higher in number and with diameters below 200 nm smaller in size than CTCs, they are easier to separate from blood cells, and their membrane protects their cargo, allowing for reproducible analysis after storage [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our experimental dataset included proteins that were determined as LC and CRC markers: TSPAN1, LGALS3BP, SLC1A5, and GPRC5A were determined in HT29 and HCT116 line-derived EVs [23], YWHAZ was revealed in HTC116-derived vesicles [32], and ICAM1, PTGFRN, DMBT1, and FN1 were identified in NCI-H23-derived EVs [33], as well as the diagnostically valuable KRAS and EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…[110]. In clinical applications, protein marker screening in plasma-derived EVs from pancreatic and lung adenocarcinoma using an aptamer array showed that a 6-protein marker panel including platelet derived growth factor subunit A, vascular endothelial growth factor C, secreted frizzled related protein 1, beta-2-microglobulin, nidogen 2, and proteasome 26S subunit 7, which is useful for cancer diagnosis and also representative in cancer hallmark functions and processes [111]. subunit alpha (PSMA) 3 and PSMA6 were further validated by western blotting as potential cancer diagnostic markers [116].…”
Section: Different Platforms For Proteomic Profilingmentioning
confidence: 99%
“…introduced a global‐scale protein array with proteome epitope tag antibody library including 62,208 antibodies that detected 15,199 peptides in proteomics [110]. In clinical applications, protein marker screening in plasma‐derived EVs from pancreatic and lung adenocarcinoma using an aptamer array showed that a 6‐protein marker panel including platelet derived growth factor subunit A, vascular endothelial growth factor C, secreted frizzled related protein 1, beta‐2‐microglobulin, nidogen 2, and proteasome 26S subunit 7, which is useful for cancer diagnosis and also representative in cancer hallmark functions and processes [111]. For protein‐binding DNA array, it solves the difficulty of protein immobilization.…”
Section: Proteomic Profiling In Evsmentioning
confidence: 99%